2011
DOI: 10.1007/s10461-011-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Online Sex-Seeking Behaviors Among Men Who have Sex with Men: Implications for Investigation and Intervention

Abstract: To investigate factors associated with online sex-seeking behaviors among men who have sex with men (MSM) in Beijing, China. MSM participants were recruited from two cohort studies with multiple enrollment methods from November 2006 to February 2007 and from March to June 2008, respectively. Data collected included demographics and sexual behaviors. Of the 901 participants, 68.1% were single; 69.3% were non-Beijing residents; 94.4% considered themselves to be homosexual; 65.2% received college or higher levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
7
15
0
Order By: Relevance
“…Our results were in line with previous studies assessing samples recruited online or offline [15,16,20,28,[34][35][36][37][38][39][40] that Chinese MSM mostly using Internet to find sex were more likely to be younger, currently single, have higher education, have higher monthly income, engage in condomless receptive anal sex, or have higher odds of being HIV-positive; while less likely to drink alcohol, use alcohol before sex, have sex with women. Our study also uniquely documented that online sex-finding MSM tended to live in the city for longer, being a registered local resident, have health insurance, ever use illicit drugs, or have fewer years in sexual activity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results were in line with previous studies assessing samples recruited online or offline [15,16,20,28,[34][35][36][37][38][39][40] that Chinese MSM mostly using Internet to find sex were more likely to be younger, currently single, have higher education, have higher monthly income, engage in condomless receptive anal sex, or have higher odds of being HIV-positive; while less likely to drink alcohol, use alcohol before sex, have sex with women. Our study also uniquely documented that online sex-finding MSM tended to live in the city for longer, being a registered local resident, have health insurance, ever use illicit drugs, or have fewer years in sexual activity.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that the Internet was the most common venue for Chinese MSM to seek male sexual partners, consistent with findings from previous studies that online AIDS Behav sex-finding has become the predominant mode among MSM in China, as in other countries [15,16,[28][29][30]. China has been experiencing vast economic and information technology developments in the past decades, allowing an unprecedented number of people to get access to Internet [28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This has been used in numerous international settings with applications such as education (Bowen, Horvath, & Williams, 2007;Gold et al, 2011;Hightow-Weidman et al, 2012;Pedrana et al, 2013), personalized information and counseling (Noar, Black, & Pierce, 2009), partner notification services (Bourne, Zablotska, Williamson, Calmette, & Guy, 2012;McFarlane, Kachur, Klausner, Roland, & Cohen, 2005), promotion of sexual health checks (Bourne et al, 2012;Friedman et al, 2014), outreach (McFarlane et al, 2005, and online testing (Klausner, Levine, & Kent, 2004). While most published studies and evaluations are based in the U.S., Australia, and Europe, there is increasing interest in internet-delivered interventions in Asia (Li et al, 2012), and a number of studies are emerging (Bao, Xiu, & Xiao, 2013;Nguyen thi, Le cong, & Van Tieu, 2013). Potential advantages and benefits include high coverage, low cost, ability to tailor interventions to personal needs and preferences, and adaptability to local contexts and population (Sullivan, Grey, & Rosser, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Asia have shown that the internet is becoming a rapidly growing environment for seeking sex 12–14. Although a number of studies12 13 have been conducted on online sex seeking among men who have sex with men, little is known about the sexual behaviours of heterosexual men who go online to seek sex partners. An understanding of their sexual risk behaviours will inform the design of interventions for this rapidly increasing group in Asia.…”
Section: Introductionmentioning
confidence: 99%